2020
DOI: 10.1038/s41598-020-70140-9
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition profile data analysis of multiple drug effects identifies endoplasmic reticulum stress-inducing ability as an unrecognized factor

Abstract: Chemicals have multiple effects in biological systems. Because their on-target effects dominate the output, their off-target effects are often overlooked and can sometimes cause dangerous adverse events. Recently, we developed a novel decomposition profile data analysis method, orthogonal linear separation analysis (OLSA), to analyse multiple effects. In this study, we tested whether OLSA identified the ability of drugs to induce endoplasmic reticulum (ER) stress as a previously unrecognized factor. After anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Alternatively, trimipramine, and possibly other compounds like lithium, may rescue lethality and larval size defects through a separate mechanism. Trimipramine induces the expression of ER stress markers, including spliced XBP1, GRP78, CHOP, and phosphorylated IRE1a in multiple cell lines [ 47 ]. Similarly, lithium treatment upregulated expression of GRP78 and the antiapoptotic protein Bcl-2 [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, trimipramine, and possibly other compounds like lithium, may rescue lethality and larval size defects through a separate mechanism. Trimipramine induces the expression of ER stress markers, including spliced XBP1, GRP78, CHOP, and phosphorylated IRE1a in multiple cell lines [ 47 ]. Similarly, lithium treatment upregulated expression of GRP78 and the antiapoptotic protein Bcl-2 [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the straightforward approach shown in Figure S1a (Supporting Information), the proposed approach reduces the costs for evaluation by restricting the candidate effects to be evaluated and systematically analyzing all possible effects by using their unsupervised and comprehensive characteristics (Figure , Figure S1b). Previously, we confirmed that decomposition profile data analysis actually identified unrecognized toxic aspects of FDA-approved drugs, while natural products were not analyzed . Thus, we analyzed transcriptome data for MCF7 cells treated with 293 compounds including natural products as derived from the CMap database with OLSA.…”
Section: Resultsmentioning
confidence: 79%
“…When a natural product is newly discovered and purified, its effects are investigated by observing the responses of culture cells treated with the compound. While the easily observable effects such as cytotoxicity and morphological changes are often observable and easily understood, the other effects are difficult to recognize and often missed . A straightforward scheme for investigating the effects of chemicals has the following flow: hypothesis formulation, construction of an assay system for testing the hypothesis, and conducting experiments with the assay system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, trimipramine, and possibly other compounds like lithium, may rescue lethality and larval size defects through a separate mechanism. Trimipramine induces the expression of ER stress markers, including spliced XBP1, GRP78, CHOP, and phosphorylated IRE1a in multiple cell lines (Morita et al, 2020). Similarly, lithium treatment upregulated expression of GRP78 and the antiapoptotic protein Bcl-2 (Hiroi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%